The Tiflis dirhams of Möngke Khān - Bennett, Kirk. (New York)
vi, 182 sayfa
Keywords: “Struck for roughly nine years starting in AH 652 (AD 1254-55), the Tiflis dirhams of Möngke have a mint formula in the four marginal obverse segments, and a date formula (including the months of the Islamic calendar) in the same four segments on the reverse. Frequent sloppy engraving of the legends, off-center strikes, and flat areas make ascertaining the dates of these dirhams problematic, and there is much confusion in the numismatic literature about which dates exist. Fortunately, various secondary features of the coins give clues for dating individual dirhams. Coins of this series display a number of stylistic differences, particularly with regard to the central decorative elements, and many of these differences are not random, but relate to specific periods. By studying many coins, one can discern patterns according to which a particular design feature was used for a while, then replaced with something else. This monograph describes these stylistic differences and uses them to create the most complete and accurate extant listing of dates and varieties for this coin series“ --